Chemical composition of essential oils of garlic (Allium sativum L.) - B RAGHAVAN, P G PRABHAKARA RAO, L JAGANMOHAN RAO (Journal of Spices and Aromatic Crops, 1999)
Six varieties of garlic grown in different geographical locations in Gujarat, India were analysed for their proximate composition including volatile oil content. Twenty nine compounds were identified in the volatile oils by gas chromatography and gas chromatography - mass spectrometry, among which 15 were new compounds hitherto not reported to be components of garlic. The relative concentrations of 13 major components in the volatile oils of all six varieties are also presented.